THE PROCESS OF CONSUMER ENGAGEMENT ON FACEBOOK FAN PAGE IN THAILAND - Trseopakol, Wasupol; Yoelao, Dusadee; Sakulku, Jaruwan (วารสารปัญญาภิวัฒน์, 2014)
Abstract Facebook fan page are the new channel in the digital era that allows consumers; (1) to interact with brands through social network connection (2) to obtain news and information and (3) to feel close with brands or products. In marketer’s point of view, consumer engagement is implemented as a key metric to gauge the effectiveness of social media. The objectives of this study are to understand consumer engagement process on facebook fan page under Thai context, to determine motivations and factors which impact the engagement with facebook fan page in different product categories, and to analyze the impact of engagement with facebook fan page on purchasing behavior. An analysis of data from 12 Thai informants in eight brand fan page indicated that the engagement process with fan page began with positive perception with the brands or products prior to visit fan page. Relevant and appealing contents on fan page such as information about brands or products or experience from other members are the key drivers for consumers to engage with the fan page while social bonding with other members does not influence on the process of building engagement because informants paid their attention on consuming information rather than interacting with others. However, the engagement did not have impact much on purchasing behaviour. Finally, Facebook fan page play a role on establishing relationship between consumers and brands. บทคัดย่อ แฟนเพจเฟซบุ๊กเป็นช่องทางใหม่ในโลกยุคดิจิตอลที่เอื้อให้ผู้บริโภคได้มี (1) ปฏิสัมพันธ์กับตราสินค้าผ่านการติดต่อแบบเครือข่ายสังคมออนไลน์ (2) ผู้บริโภคสามารถรับข้อมูลข่าวสาร และ (3) รู้สึกใกล้ชิดกับตราสินค้ามากขึ้น ทำให้นักการตลาดสมัยใหม่ได้ประยุกต์เรื่องความผูกพันของผู้บริโภค (Consumer Engagement) เป็นเครื่องชี้วัดถึงประสิทธิผลของสื่อออนไลน์ การศึกษาเรื่องความผูกพันของผู้บริโภคไทย ต่อการใช้งานแฟนเพจเฟซบุ๊กมีจุดมุ่งหมายเพื่อเข้าใจกระบวนการความผูกพัน และปัจจัยที่ส่งผลต่อความผูกพันของผู้บริโภคแฟนเพจเฟซบุ๊กภายใต้บริบทสังคมไทยในหมวดสินค้าที่แตกต่างกัน นอกจากนี้ยังวิเคราะห์ถึงผลของความผูกพันของแฟนเพจเฟซบุ๊กที่มีต่อความตั้งใจซื้อหรือบริการ โดยผู้วิจัยได้ใช้การวิจัยเชิงคุณภาพโดยการสัมภาษณ์ (Qualitative Interview) กับผู้บริโภคที่มีการใช้แฟนเพจของสินค้า และบริการต่างๆ เป็นประจำ (Active) จำนวนทั้งสิ้น 12 ท่านที่เข้าเยี่ยมชมแฟนเพจสินค้าหรือบริการใน 8 หมวดสินค้า ผลการวิจัยพบว่า กระบวนการความผูกพันเริ่มขึ้นเมื่อผู้บริโภครู้สึกดีกับตราสินค้า หรือสินค้านั้นก่อนการ เริ่มใช้งานแฟนเพจ เนื้อหาที่ปรากฏบนแฟนเพจเป็นแรงขับให้ผู้บริโภครู้สึกผูกพันกับแฟนเพจนั้น โดยเฉพาะอย่างยิ่งเมื่อเนื้อหาที่สามารถตอบสนองความต้องการพื้นฐานด้านข้อมูลของผู้บริโภค เช่น ข้อมูลใหม่ๆ ของสินค้าหรือบริการ นอกจากนี้ผลการวิจัยยังพบว่าความใกล้ชิดกับสมาชิกคนอื่นๆ บนแฟนเพจไม่มีอิทธิพลกับกระบวนการในการสร้างความผูกพันกับแฟนเพจต่างๆ เนื่องจากความสนใจของผู้บริโภคต่างมุ่งเน้นที่การบริโภคข่าวสารที่ปรากฏบนแฟนเพจมากกว่าการรู้จักคนอื่นๆ ในท้ายสุดผู้เข้าร่วมวิจัยเปิดเผยว่าการสร้างความผูกพันบนแฟนเพจไม่ส่งผลต่อพฤติกรรมการซื้อสินค้ามากนัก แต่มองว่าการได้เข้าไปใช้งานแฟนเพจเฟซบุ๊ก มีส่วนสำคัญในการสร้างความสัมพันธ์ที่ดีระหว่างตราสินค้าและผู้บริโภค